2017
DOI: 10.1002/brb3.877
|View full text |Cite
|
Sign up to set email alerts
|

Action video gaming and the brain: fMRI effects without behavioral effects in visual and verbal cognitive tasks

Abstract: IntroductionIn this functional magnetic resonance imaging (fMRI) study, we compared task performance together with brain activation in a visuospatial task (VST) and a letter detection task (LDT) between longtime action video gamers (N = 14) and nongamers (N = 14) in order to investigate possible effects of gaming on cognitive and brain abilities.MethodsBased on previous research, we expected advantages in performance for experienced action video gamers accompanied by less activation (due to higher efficiency) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Evidence for lateralization related to specific movement has already been well described in the literature (65,66). What is more, the observed result is consistent with the findings of other researchers, who showed that action video game players in comparison to non-players are characterized by faster reaction times in tasks that measure visual and spatial abilities, but only when responses were given using the non-dominant hand (67). It should be mentioned that we did not observe a relationship between the size of the lenticular nucleus and experience with RTS games.…”
Section: Abbreviations: Sc2 -Starcraft IIsupporting
confidence: 91%
“…Evidence for lateralization related to specific movement has already been well described in the literature (65,66). What is more, the observed result is consistent with the findings of other researchers, who showed that action video game players in comparison to non-players are characterized by faster reaction times in tasks that measure visual and spatial abilities, but only when responses were given using the non-dominant hand (67). It should be mentioned that we did not observe a relationship between the size of the lenticular nucleus and experience with RTS games.…”
Section: Abbreviations: Sc2 -Starcraft IIsupporting
confidence: 91%
“…74,75 What is more, there is a study showing that action video game players are characterized by faster reaction times in tasks that measure visual and spatial abilities (in comparison with nonplayers), but only when responses were given using the nondominant hand. 76 It should be mentioned that we did not observe a relationship between the size of the LN and experience with RTS games. Other studies 12,77,78 have similarly failed to show such correlations, suggesting that the relationship between anatomical plasticity measured using VBM methods and behavior may be more complex and mediated by other variables.…”
Section: Discussionmentioning
confidence: 55%
“…AVGPs outperformed NGs on measures of visual and spatial aspects of information processing speed. Moreover, despite failing to find differences in overall task performance, an fMRI study by Richlan and colleagues [ 104 ] identified a significant increase in the blood oxygen level dependent (BOLD) signal in frontoparietal regions from baseline to post-test, reflecting increased neural engagement in AVGPs compared to NGs. According to Laplace’s rule of succession, a future study would have a 93.75% chance of finding AVGPs to show superior information processing ability compared to NGs.…”
Section: Resultsmentioning
confidence: 99%